2021
DOI: 10.1098/rsos.210749
|View full text |Cite
|
Sign up to set email alerts
|

How the African house gecko (Hemidactylus mabouia) conquered the world

Abstract: Alien species are among the greatest threats to biodiversity, but the evolutionary origins of invasiveness remain obscure. We conducted the first range-wide sampling of Hemidactylus mabouia from more than 120 localities across Africa, Madagascar and the Neotropics to understand the evolutionary history of one of the most widely distributed, invasive vertebrates in the world. We used a multi-locus phylogeny, species delimitation, fossil-calibrated timetree, ancestral area reconstruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 68 publications
(115 reference statements)
3
19
0
Order By: Relevance
“…Our results show that both H. mabouia ss and H. mercatorius occur in the Caribbean, where the presence of H. mercatorius (in at least Cuba and both the British and US Virgin Islands) represents a novel finding. We also note that Agarwal et al [34] did not detect H. mercatorius in the Gulf of Guinea, as reported by Rocha et al [36]. Studies of the H. mabouia-mercatorius complex to date have used different mtDNA loci (e.g., 16S [37], ND2 [34], and COI [39] and this study), which prohibits direct comparison of their results.…”
Section: Squamata-lizards (Excluding Snakes)supporting
confidence: 51%
See 4 more Smart Citations
“…Our results show that both H. mabouia ss and H. mercatorius occur in the Caribbean, where the presence of H. mercatorius (in at least Cuba and both the British and US Virgin Islands) represents a novel finding. We also note that Agarwal et al [34] did not detect H. mercatorius in the Gulf of Guinea, as reported by Rocha et al [36]. Studies of the H. mabouia-mercatorius complex to date have used different mtDNA loci (e.g., 16S [37], ND2 [34], and COI [39] and this study), which prohibits direct comparison of their results.…”
Section: Squamata-lizards (Excluding Snakes)supporting
confidence: 51%
“…The authors suggested that the H. mabouia complex may be composed of more than 20 putative species, ranging throughout sub-Saharan Africa to the Caribbean, with H. mabouia sensu stricto (ss) ranging from Ghana through the Congolian and northern Zambezian regions, the South African and extreme southern Zambezian regions, and the neotropics. Hemidactylus mabouia ss was found to be sister to H. mercatorius, and this H. mabouia ss + H. mercatorius clade was nested within several clades of H. mabouia sensu lato (sl), which included several additional samples from the Zambezian and South African regions [34]. Our dataset includes some of the same H. mabouia specimens sequenced by Agarwal et al [34] from the Republic of Congo, which represent H. mabouia ss, as does our sample from Puerto Rico and one (of two) from the US Virgin Islands.…”
Section: Squamata-lizards (Excluding Snakes)mentioning
confidence: 92%
See 3 more Smart Citations